FORMULASI TABLET PARASETAMOL DENGAN KOMBINASI PVP DAN AMILUM UMBI PORANG (Amorphopallus onchopyllus) SEBAGAI BAHAN PENGIKAT TERHADAP SIFAT FISIK TABLET - Arinda Nur Cahyani; Adi Susanto; Iva Rinia Dewi; Iswatun Nurhikmah (Program Studi Farmasi, Universitas Muhadi Setiabudi, 2023)
Tablets are the most widely used preparations, this is because tablets have advantages that other pharmaceutical preparations do not have, both in terms of production, storage, distribution, and use. This study aims to determine the concentration of PVP and starch from porang tubers which can be used as a binder in the preparation of paracetamol tablets and to determine the combination of PVP and starch from porang tubers as a binder to the physical properties of paracetamol tablets. In this study, 4 paracetamol tablet formulas with PVP binder were made combined with porang tuber starch with a weight of 650 mg per tablet. The binder used was PVP in each formula, namely F1 0%, F2 1%, F3 3%, and F4 5%, and porang tuber starch in each formula was F1 5%, F2 0%, F3 6%, and F4 7%. Tablets were made using wet granulation, the granules obtained were tested for their physical properties. including moisture content, flow time, angle of repose, and compressibility. After the powder mixture was compressed with a hardness between 4-8 kg, the resulting tablets were then tested for their physical properties including weight uniformity, size uniformity, friability, hardness, and disintegration time. The tablets produced from all formulas met the uniformity of weight, uniformity of size, and friability, the hardness that met the physical properties of the tablets was only found in formula I, which was 7.30 kg, and the fastest disintegration time in formula I was 9.6 minutes.